Identifying Equity Market Integration : A Study of NIFTY-50 and the World’s Top Six Indices - Vodwal, Sandeep; Sawaliya, Priya (Indian Journal of Research in Capital Markets, 2025)
Purpose : The decoupling theory proposed the benefits of internationally diversified portfolios to mitigate investment risk for global investors. The global investment risk was observed to be inversely related to the degree of co-movement of the stock indices. Therefore, the current study attempted to seek the answer to whether the stock indices of the world’s top seven countries were independent or exhibited a lead–lag relationship. Methodology : The study employed the Johannesburg co-integration and Granger-causality to investigate the relationship for the monthly returns data starting from 1st January 1995 and ending on 31st March 2025. Findings : The study found that the Indian index was co-integrated in the long run with American, Chinese, British, Japanese, and Canadian stock indices ; whereas, in the short-run, it was significantly influenced by the US markets and followed the returns patterns. Theoretical, Managerial, and Practical Implications : The performance of the US market was taken as a proxy for the Indian market in the short run, and the performance of the Indian market affected the markets in the UK, Canada, and French stock indices. Originality: The current study reported the interlinkages of the Indian stock market with the top six developing and developed economies of the world.